Smart bus stop / Ahmad Zakwan Mohd Nor and Faiq Izzuddin Isadin - Mohd Nor, Ahmad Zakwan; Isadin, Faiq Izzuddin (2015)
Bus stop is a place where people use to wait for any transportation to arrive. Typical design of a bus stop is not very comfortable for people. It doesn't have any proper fan and lighting. Sometime people don't notice transportation is arriving at the bus stop. At night without any lighting the bus stop will be so dark and crime rate can increase at bus stops. Thus this project is created to ease and give comfortable for people who are waiting for the public transportation at the bus stop. When people come to the bus stop, ultrasonic sensor will detect and activate LDR sensor and temperature sensor. LOR sensor will switch on the lamp during night time. Next, temperature sensor will activate the fan during in hot condition. Fan and lamp will automatically switch off when there are no people at the bus stop. Besides that, the arrival of the bus can be detects by using transceiver. When the bus is near the bus stop, transceiver will activate the buzzer so that people will notice the bus that will arrive. It is hope that this project can create comfortable surroundings to people that is using the bus stop to wait for any public transportation.